Cultura de segurança do paciente e sua interface com o desenvolvimento de práticas seguras: da percepção à avaliação - Passos, Ana Cláudia de Brito (2021)
Introduction. The culture of patient safety is the basis for the development of safe processes and better outcomes for patients, as it favors the implementation of safe practices. Understanding it influences the possibility of making changes in the management of organizational security. Goal. To evaluate the patient safety culture based on the perceptions and practices of professionals working in a public hospital in northeastern Brazil. Method. It is a quantitative and qualitative research that was divided into three phases, with different methods of approach, contemplating the aspects that involve the culture of patient safety and safe practices. The sample consisted of professionals who were employed by the hospital. The data collection instruments were the Hospital Survey on Patient Culture (HSOPSC); the Health Care Risk Management Assessment questionnaire (AGRASS), document analysis, scripts for participant observation and interviews. For data analysis, different techniques were used, descriptive and inferential statistics and also the analysis of categorical and lexical content, the latter with the aid of the Iramuteq software. Results. The culture of patient safety is positive among 47.2% of professionals and the dimensions “Expectations and actions to promote safety of supervisors / managers” (68%), “Organizational learning and continuous improvement” (67%) and “Work in teams in the units ”(66%) were the ones with the highest percentages of positive responses. The dimensions “Non-punitive response to error” (20%) and “Personnel dimensioning (31%) were the ones that need improvement. The testimonies and comments of the professionals allowed a better understanding of the safety culture and its interface with safe practices, in addition to the identification of organizational contextual aspects, where from the interpretative analysis three categories emerged: Leadership actions focused on safety patient; Assistance team actions for safe care and Learning practices that reinforce safe behaviors. As for safe management practices, there were gaps in the incorporation of Standard Operating Procedures and protocols. Regarding safe care practices, weaknesses were found in most of the findings, highlighting hand hygiene and prescription, use and administration of medications. Conclusions. The results reveal an incipient safety culture and safe care and management practices that have not been fully adopted.